Development and psychometric evaluation of a quality of work life scale for professional nurses in primary care - Wasana Boonyamanee; Araya Prasertchai; Natnaree Aimyong; Worrawit Nakpan (Journal of Public Health and Development, 2026)
Quality of Work Life (QWL) significantly impacts nurse retention, organizational effectiveness, and healthcare delivery. This research centered on the development and psychometric evaluation of an instrument designed to measure the QWL of professional nurses in Thailand's primary care facilities. The evaluation focused on establishing its content validity, construct validity, and reliability. A sample of 400 professional nurses was selected via multi-stage sampling from primary healthcare units in Thailand. The instrument's content was synthesized from various QWL theories. Utilizing a mixed-methods approach, the study began with semi-structured interviews with subject matter experts. The qualitative data gathered from these interviews were subsequently validated through triangulation. These findings informed the development of the quantitative structured questionnaire. The developed instrument underwent rigorous validation. The final 77-item, 8-dimension instrument, structured as a 5-point Likert-scale questionnaire, demonstrated a Content Validity Index (CVI) of 0.82 and a Cronbach’s alpha of 0.886. Exploratory factor analysis (EFA) revealed a Kaiser-Meyer-Olkin (KMO) value of 0.901 and a significant Bartlett’s Test of Sphericity (p < 0.001). Varimax orthogonal rotation yielded eight components with eigenvalues greater than 1, explaining 67.28% of the total variance. Confirmatory factor analysis (CFA) indicated a strong model fit (χ² = 523.472, df = 160, p = 0.056; CFI = 0.972; SRMR = 0.035; RMSEA = 0.045). The integration of qualitative insights from expert interviews supports the conclusion that the new QWL instrument corresponds effectively with empirical data. It demonstrates robust reliability and validity while also reflecting the unique context of professional nurses in primary care. Nursing policymakers can utilize this tool to monitor and improve the QWL among nurses, potentially leading to enhanced job satisfaction, retention, and healthcare service quality.